The Impact of Corporate Culture and Work Ethics on Organizational Innovation in Higher Education Institutions in Sulaymaniyah Sulaymaniyah Polytechnic University as an Example - Talar Jalal Karim; Faraidun Faizulla Aziz; Diyar Muhammed Sidiq Abdalla (Eurasian Journal of Management & Social Sciences)
This study explores the origins of corporate culture and work ethics and offers definitions and types of innovation. It also proposes a conceptual framework to show how corporate culture, work ethics, and organizational innovation are correlated. The study then adds hypotheses regarding corporate and ethical values and innovation. In total, 130 Sulaimani Polytechnic University employees participated in the survey and the collected data were analyzed to test the proposed research hypotheses. It concludes that in service corporations, a higher education institution in this context, organizational innovation can be positively affected by corporate culture and work ethics.